2021
DOI: 10.1038/s41438-020-00450-6
|View full text |Cite
|
Sign up to set email alerts
|

Integration of full-length transcriptomics and targeted metabolomics to identify benzylisoquinoline alkaloid biosynthetic genes in Corydalis yanhusuo

Abstract: Corydalis yanhusuo W.T. Wang is a classic herb that is frequently used in traditional Chinese medicine and is efficacious in promoting blood circulation, enhancing energy, and relieving pain. Benzylisoquinoline alkaloids (BIAs) are the main bioactive ingredients in Corydalis yanhusuo. However, few studies have investigated the BIA biosynthetic pathway in C. yanhusuo, and the biosynthetic pathway of species-specific chemicals such as tetrahydropalmatine remains unclear. We performed full-length transcriptomic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…The important intermediate ( S )-reticuline that acts as the central branch point of several BIAs is then synthesized from ( S )-norcoclaurine through the catalysis of four enzymes: 6OMT, CNMT, NMCH, and 4′OMT [ 67 , 72 76 ]. Finally, magnoflorine (yellow), sanguinarine (blue), and berberine (green) are produced from ( S )-reticuline through the catalysis of multiple enzymes [ 15 , 64 , 77 ]. Genome-wide analysis predicted 91 nonredundant genes that were probably involved in the biosynthesis of BIAs in A. contorta ( Table S10 ).…”
Section: Resultsmentioning
confidence: 99%
“…The important intermediate ( S )-reticuline that acts as the central branch point of several BIAs is then synthesized from ( S )-norcoclaurine through the catalysis of four enzymes: 6OMT, CNMT, NMCH, and 4′OMT [ 67 , 72 76 ]. Finally, magnoflorine (yellow), sanguinarine (blue), and berberine (green) are produced from ( S )-reticuline through the catalysis of multiple enzymes [ 15 , 64 , 77 ]. Genome-wide analysis predicted 91 nonredundant genes that were probably involved in the biosynthesis of BIAs in A. contorta ( Table S10 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to fusion expression with hydrophilic chaperons, we can also focus on searching for orthologous BBE candidates (X. Liu et al, 2017;Xu et al, 2021) or improving BBE activity via protein engineering to optimize the sanguinarine biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al found that BBE was mainly expressed as inclusion bodies in Escherichia coli and the functional expression level could be significantly increased by fusion expression with maltose binding protein and glutathione S‐transferase (W. Zhao et al, 2021). In addition to fusion expression with hydrophilic chaperons, we can also focus on searching for orthologous BBE candidates (X. Liu et al, 2017; Xu et al, 2021) or improving BBE activity via protein engineering to optimize the sanguinarine biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Gene cloning and functional characterization of these candidate CYP450s will be performed in our subsequent study. Compared with the BIAs production plants, such as Coptis chinensis ( He et al, 2018 ) and Corydalis yanhusuo ( Xu et al, 2021 ), tetrandrine was the unique compound of S. tetandra . However, the gene related to this biosynthesis pathway was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, transcriptome analysis and metabolic profiling have been extensively used to explore and identify critical genes related to the biosynthesis and regulation of secondary metabolites in medicinal plants, such as Gloriosa superba ( Nett et al, 2020 ), Cinnamomum camphora ( Chen et al, 2018 ), and Atractylodes macrocephala ( Ruan et al, 2021 ). Using this integrative approach, several crucial genes ((S)-coclaurine N-methyltransferase, (S)-N-methylcoclaurine-3-hydroxylase) have been identified in Corydalis yanhusuo ( Xu et al, 2021 ), Coptis deltoidea ( Zhong et al, 2020 ), and Erythrina velutina Willd ( Chacon et al, 2021 ). These results shed light on the biosynthesis of BIAs in S. tetrandra .…”
Section: Introductionmentioning
confidence: 99%